(untitled) (Fiep Bulletin - online, 2013)
Physical Education has been establishing a closer relationship to the public health system in order to enlarge the scope of basic care acting especially concerning the development of actions towards health promotion and damages prevention. This study aims to conduct na integrative review on scientific articles reporting Physical Education in public/community health especially in basic care context. Thirty-two articles from 2000 and 2010 were selected. Such articles were divided into five issues: studies to provide theoretical basis to thoughts on Physical Education/Public health relationship (11 articles); Physical Education professional in order to act in the public health system (2); studies to set a direct relationship with basic care spaces (10); studies taking place at a basic care unit (7); and finally studies discussing the relationship between Physical Education and SUS through National Policy for Health Promotion (2). We conclude that the relationship between Physical Education and public/community health was the focus of many studies in the XXI century first decade, however such relationship still lacks studies in different areas in order to provide Physical Education professionals in basic care with a greater theoretical and practical basis.